Faktor-faktor yang berhubungan dengan pemanfaatan pos pembinaan terpadu penyakit tidak menular (POSBINDU PTM) - Evi Mefriyanti; Wayan Aryawati; Dina Dwi Nuryani (Holistik Jurnal Kesehatan, 2023)
Background: Non-communicable diseases are also known as chronic diseases, they are not transmitted from person to person. Based on data from the Tulang Bawang Regency, it is known that there are 16 Public Health Centers, with the highest achievement at the Kartaharja Health Center at 85.6 percent and the lowest at the Panaragan Health Center at 16.7 percent for the Margakencana Health Center at 17.5 percent and the Daya Murni Health Center at 18.9 percent.Purpose: To find out the factors related to the utilization of Integrated Healthcare Services for Non-Communicable Diseases.Method: Quantitative with a cross-sectional approach, the research will be conducted in the Working Area of the Margakencana Health Center in West Tulang Bawang Regency which will be held in June 2021. The population in this study is the community in the Work Area of the Margakencana Health Center in West Tulang Bawang Regency who suffer from hypertension and diabetes mellitus as many as 1274 Soul, with a sample of 265 people by purposive sampling. Collecting data using questionnaires, data analysis using univariate, bivariate (chi-square), and multivariate.Results: There is no relationship between education (p-value = 0.375) and access to health (p-value = 0.254). There is a relationship between perception (p-value = 0.002), occupation (p-value = 0.000), the role of health workers (p-value = 0.001), and family support (p-value = 0.013).Conclusion: There is a significant relationship among variables perception, occupation, the role of health workers, and, family support.Suggestion: It is hoped that health workers will be able to change Integrated Healthcare Services for Non-Communicable Diseases operational hours from 8 am to 8 pm so that people can carry out examinations not only at one time.Keywords: Utilization; Integrated Healthcare Services for Non-Communicable Diseases; Public Health CenterPendahuluan: Penyakit tidak menular (PTM) dikenal juga sebagai penyakit kronis, tidak ditularkan dari orang ke orang.Berdasarkan data dari Kabupaten Tulang Bawang diketahui bahwa terdapat 16 Puskesmas, dengan pencapaian keaktifan tertinggi di Puskesmas Kartaharja sebesar 85,6 persen dan terendah di Puskesmas Panaragan sebesar 16,7 persen untuk Puskesmas Margakencana sebesar 17,5 persen dan Puskesmas Daya Murni sebesar 18.9 persen.Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan pemanfaatan pos pembinaan terpadu penyakit tidak menular (Posbindu PTM) Di Wilayah Kerja Puskesmas Margakencana Kabupaten Tulang Bawang Barat Tahun 2021.Metode: Kuantitatif dengan pendekatan cross sectional, penelitian akan dilakukan di Wilayah Kerja Puskesmas Margakencana Kabupaten Tulang Bawang Barat yang dilaksanakan pada bulan Juni  2021. Populasi pada penelitian ini masyarakat di Wilayah Kerja Puskesmas Margakencana Kabupaten Tulang Bawang Barat yang mengalami sakit hipertensi dan diabetes mellitus sebanyak 1274 Jiwa, dengan sampel sebanyak 265 orang secara purposive sampling.Pengumpulan data dengan kuesioner, analisis data secara univariat, bivariat (chi square) serta multivariat.Hasil: Tidak ada hubungan pendidikan (p-value = 0,375) dan akses kesehatan (p-value = 0,254). Ada hubungan Persepsi (p-value = 0,002), pekerjaan (p-value = 0,000), peran petugas kesehatan (p-value = 0,001), dukungan keluarga (p-value = 0, 013).Simpulan: Ada hubungan yang signifikan antara variabel persepsi, pekerjaan, peran tenaga kesehatan, dan dukungan keluarga.Saran: Diharapkanbagi tenaga kesehatan untuk dapat mengubah jam operational posbindu dari jam 8 pagi sampai jam 8 malam sehingga masyarakat dapat melakukan pemeriksaan tidak hanya dalam satu waktu